2017
DOI: 10.18632/oncotarget.21424
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian herbal medicine prevents hypertension-induced left ventricular hypertrophy by diminishing NADPH oxidase-dependent oxidative stress

Abstract: Indonesian herbal medicine Centella asiatica, Justicia gendarussa and Imperata cylindrica decoction (CJID) are known to be efficacious for hypertension. Oxidative stress plays an important role in hypertension-induced left ventricular hypertrophy (H-LVH). This study evaluated whether CJID inhibit cardiac remodeling in spontaneously hypertensive rats (SHRs) through mechanism of oxidative stress-related cardiac-NADPH oxidase (NOXs) pathway: NOX1, NOX2 and NOX4. Forty-weeks-old SHRs and normotensive-WKY rats, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
1
13
0
3
Order By: Relevance
“…LDL is also known as bad cholesterol because its increase is linked to an increase in cardiovascular risk. The decrease of this particular lipid level by ICR confirms the results of the work of Mak-Mensah et al [32], Rouslin et al [33] and Sulistyowati et al [34] which showed that the plant used in this study is effective against a cardiovascular disorder such as hypertension, since it is widely accepted that hypertension is associated with an increased blood levels of low-density lipoprotein (LDL).…”
Section: Discussionsupporting
confidence: 90%
“…LDL is also known as bad cholesterol because its increase is linked to an increase in cardiovascular risk. The decrease of this particular lipid level by ICR confirms the results of the work of Mak-Mensah et al [32], Rouslin et al [33] and Sulistyowati et al [34] which showed that the plant used in this study is effective against a cardiovascular disorder such as hypertension, since it is widely accepted that hypertension is associated with an increased blood levels of low-density lipoprotein (LDL).…”
Section: Discussionsupporting
confidence: 90%
“…Researches have indicated that the active ingredients of CJI are potential; it not only prevents hypertension-induced heart disease but also inhibits vascular remodeling. 11 , 48 , 49 The oral administration of CJI decoction for five weeks reduced systolic blood pressure in SHR by 24.2% at the end of the study, and the average blood pressure lowering was at 51.3 points. 11 CJI contains so many active ingredients that function as radical scavenging activities.…”
Section: Discussionmentioning
confidence: 95%
“… 11 , 48 , 49 The oral administration of CJI decoction for five weeks reduced systolic blood pressure in SHR by 24.2% at the end of the study, and the average blood pressure lowering was at 51.3 points. 11 CJI contains so many active ingredients that function as radical scavenging activities. Rich content of polyphenols from CJI show an important antioxidant activity.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations